Clinical Effectiveness of Rivastigmine Monotherapy and Combination Therapy in Alzheimer's Patients. (4th December 2012) - Sonali, Nirmal; Tripathi, Manjari; Sagar, Rajesh; Velpandian, Thirumurthy; Subbiah, Vivekanandhan
Summary: Background: Rivastigmine is an acetylcholinesterase inhibitor; the genotype data seen alongside the phenotype data explain the mutation or the molecular genetics involved and also help to relate the phenotype of an individual with their genotype. Aim: To determine the clinical effectiveness of CYP2D6, CYP3A4, CYP2C9/19, and UGT polymorphism on the steady‐state plasma concentrations and therapeutic outcome of rivastigmine monotherapy and combination therapy in patients with Alzheimer's disease. Result: In this study, a significant allele frequency was observed for CYP2D6*3 polymorphism in patients under rivastigmine combination therapy (A>del = 0.50 [patients] and A>del = 0.20 [controls]), UGT2B7 (T = 0.17 [patients] and 0.33 [Controls], and UGT1A9*5 A = 0.58 [patients] and 0.26 [Controls]). The drug levels and P value of responders/nonresponders were found to be 0.17 ± 0.08/0.22 ± 0.16 and 0.574 for rivastigmine and 0.18 ± 0.11/0.66 ± 0.63 and 0.009 for rivastigmine in combination therapy and 1.40 ± 0.65/0.59 ± 0.84 and 0.05 for memantine in combination therapy. Conclusion: Poor metabolizer subjects of UGT2B7 polymorphism in patients under rivastigmine combination therapy have higher drug levels with a poor response to the drug treatments.